The use of social networking and learning management systems in English language teaching in higher education. Issue 4 (29th July 2014) - Dogoriti, Evriklea; Pange, Jenny; S. Anderson, Gregory
Abstract : Purpose: – The use of web-enhanced teaching of the English as a foreign language in higher education in Greece is addressed in this case study which examines the student's perceptions of online instruction using Moodle as a learning management system (LMS), with and without the use of Facebook (FB) as an adjunctive learning platform. The merging of this collaborative and interactive social platform with a LMS is explored, examining the attitudes of higher education foreign language learners toward Moodle as a LMS, and FB as an adjunctive informal learning environment. The paper aims to discuss these issues. Design/methodology/approach: – Results are drawn from a pre-FB questionnaire after a term using Moodle only, and a post-FB questionnaire following a term using Moodle and FB. Findings: – Results suggest that the use of web-based tools and social media changed the way students viewed the role of internet technology in the development of their English language learning. Most students (76 percent) agreed that the addition of FB to the course helped build a sense of community within a learning environment, while 69 percent suggested it enhanced the learning process. Originality/value: – Results suggest FB may reinforce communication skills and engagement in the learning process and may support participation and collaborative learning in the formal learning environment provided by Moodle.